Adaptation of .NET MVC framework in developing an agriculture sources inventory system / Ray Adderley Jm Gining ... [et al.] - Jm Gining, Ray Adderley; Mohd Fauzi, Shukor Sanim; Jamaluddin, Nabil Fikri; Mohd Azmi, Nursyamimi Aima; Hashim, Muhamad Arif; Mohd Fuzi, Mohd Faris; Ibrahim, Alif Faisal (UiTM Cawangan Perlis, 2018)
A viable inventory management system is crucial to an organization, especially those who deals with stock going in and out of their premise. The system should cover several aspects in managing the collection of the available stocks to ensure efficiency. An inventory management system comprises crucial functions that the goal is to produce accurate information –a minor mis-information could lead to a wrong decision making. Improper system design could lead to the problem; thus, the design of this inventory system is supported by .NET Model View Controller (MVC) Framework as its backbone. The .NET MVC Framework is one of the most widely used framework that is written in C# programming language. By utilizing the MVC Framework, its three main components; data model (Model), user interface (View), and business logic (Controller) can be managed separately without affecting the entire system. Thus, the risk of the system functions to produce inaccurate information is reduced significantly. Moreover, MVC also supportsscalability, extend-ability and maintainability which is a very important aspect for an information system with growing needs of new functions.